Corpus Callosum Size and Verbal Intelligence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Quantitative MRI measurements of the sagittal surface area of the corpus callosum (CC) in 72 preterm individuals tested at adolescence (14-15 years) were compared with verbal skills on neuropsychological tests in a study at the Institute of Psychiatry, De Crespigny Park, London, UK.